Monitoramento das águas da bacia hidrográfica pirangi pela determinação dos índices de qualidade da água-iqa e índice de toxidez-it - Lima, Maria Santana Bezerra de (2010)
The problems of water supply in Northeast Brazil are severe and require more focused studies. This work was intended to assess water quality in the watershed Pirangi, located in the Northeastern state of the newborn using the Water Quality Index, AQI associated with the Index of Toxicity-IT. The data presented in this study were collected in November 2008, June 2009 and March 2010 at eight sampling stations distributed throughout the basin. The study covered nine parameters, based on guidelines established by CETESB, and seven members of Metal Toxicity index-IT. These waters are framed in the classification between GOOD and BAD showing AQI 41.34 minimum and a maximum of 76.23. Virtually all seven metals analyzed were below the detection limits of ICP-OES giving IT a water equal to one when they are absent and 0 when there are levels of trace metals